Clinical significance of low forced expiratory flow between 25% and 75% of vital capacity following treated pulmonary tuberculosis: a cross-sectional study. Issue 7 (23rd July 2014) - Pefura-Yone, Eric Walter; Kengne, Andre Pascal; Tagne-Kamdem, Pierre Eugene; Afane-Ze, Emmanuel
Abstract : Objectives: The aim of this study was to assess the prevalence and determinants of post-tuberculosis chronic respiratory signs, as well as the clinical impact of a low forced expiratory flow between 25% and 75% (FEF25–75% ) in a group of individuals previously treated successfully for pulmonary tuberculosis. Design: This was a cross-sectional study involving individuals in their post-tuberculosis treatment period. They all underwent a spirometry following the 2005 criteria of the American Thoracic Society/European Respiratory Society. Distal airflow obstruction (DAO) was defined by an FEF25–75% <65% and a ratio forced expiratory volume during the first second (FEV1 )/forced vital capacity (FVC) ≥ 0.70. Logistic regression models were used to investigate the determinants of persisting respiratory symptoms following antituberculous treatment. Setting: This study was carried out in the tuberculosis diagnosis and treatment centre at Yaounde Jamot Hospital, which serves as a referral centre for tuberculosis and respiratory diseases for the capital city of Cameroon (Yaounde) and surrounding areas. Participants: All consecutive patients in their post-tuberculosis treatment period were consecutively enrolled between November 2012 and April 2013. Results: Of the 177 patients included, 101 (57.1%) were men, whose median age (25th-75th centiles) was 32 (24–45.5) years. At least one chronic respiratory sign was present in 110 (62.1%) participants and DAO was found in 67 (62.9%). Independent determinants of persisting respiratory signs were the duration of symptoms prior to tuberculosis diagnosis higher than 12 weeks (adjusted OR 2.91; 95% CI 1.12 to 7.60, p=0.029) and presence of DAO (2.22; 1.13 to 4.38, p=0.021). Conclusions: FEF25–75% <65% is useful for the assessment and diagnosis of post-tuberculous DAO. Mass education targeting early diagnosis of pulmonary tuberculosis can potentially reduce the prevalence of post-tuberculosis respiratory signs and distal airflow obstruction.